United Arab Emirates : Technical Assistance Report - Liquidity Management and Forecasting. (IMF Staff Country Reports; Country Report, 2022)
The new Dirham Monetary Framework developed by the Central Bank of the United Arab Emirates (CBUAE) operationalizes a floor system and provides a complete set of instruments to manage liquidity under a fixed exchange rate arrangement and capital mobility. This technical assistance report presents an overview of this operational framework and a set of recommendations to streamline and further improve it especially with regards to: (i) the discontinuation of the FX swap facility; (ii) the issuance of central bank bills; (iii) the design of fine-tuning operations; and (iv) the design and calibration of the reserves requirements. Moreover, the report provides a complete liquidity forecasting infrastructure, using cutting-edge statistical methods, to project the changes in the supply of banks reserves through the forecast of the three main autonomous factors. It also offers a statistical approach to estimate the optimal liquidity surplus and calibrate the operational mix between the different liquidity absorptions instruments. At last, the report investigates the functioning and structure of the UAE money markets.